About risks of losses and it's evaluation - Данилюк, М. О.; Лагдан, В. А. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Business risk is considered in the context of the danger of resources’s losses and results of operations. The classification of losses’s types and their characteristics are presented. Some areas of risk indicators to assess the amount of risk, as well as features of the probability distribution of occurrence of a certain level of losses are highlighted. The curve of the probability distribution of possible losses is plotted, which will help prevent them in the future.